Continuous positive airway pressure adherence and blood pressure lowering in patients with obstructive sleep apnoea syndrome and nocturnal hypertension. (4th July 2021) - Xia, Jia-Hui; Kang, Yuan-Yuan; Cheng, Yi-Bang; Huang, Qi-Fang; Xu, Ting-Yan; Li, Yan; Wang, Ji-Guang
Abstract: Purpose: We investigated continuous positive airway pressure (CPAP) adherence and its association with the blood pressure (BP) and pulse rate changes in patients with obstructive sleep apnoea syndrome (OSAS) and hypertension. Materials and methods: In a single-blind trial, patients were randomly assigned to CPAP or sham CPAP treatment for 3 months. We performed clinic, ambulatory and home BP measurements at baseline and during follow-up. CPAP adherence was assessed as the CPAP frequency per week and time per night. Non-adherence was defined as a CPAP use for <5 days/week or <4 h/night. Results: In the CPAP ( n = 26) and sham CPAP groups ( n = 21), the CPAP frequency was 5.5 and 4.8 days/week ( p = 0.17), respectively, and the CPAP time was 5.0 and 4.1 h/night ( p = 0.03), respectively. The corresponding prevalence of non-adherence was 46.2% and 66.7% ( p = 0.16), respectively. The CPAP frequency but not time tended to be associated with the changes in BP and pulse rate at 3 months of follow-up, especially home systolic/diastolic BP in the CPAP group (3.2/1.3 mmHg greater reductions per 1 day increment, p ≤ 0.01). Adherent, compared with non-adherent patients, had greater reductions in BP or pulse rate at 3 months of follow-up. In the CPAP and sham CPAP groups combined, statistical significance was achieved for the adjusted between adherence and non-adherence differences in home systolic/diastolic BP (–5.0/–3.8 mmHg) and 24-h, daytime and night-time ambulatory pulse rate (–6.2, −7.8 and −4.4 beats/min, respectively, p ≤ 0.04). Conclusion: CPAP adherence was associated with the BP lowering and pulse rate slowing effects, especially the CPAP frequency.